Transformational Leadership (TFL) dan Subjective Well-Being (SWB) pada Karyawan Produksi PT. X Salatiga - Wisnu Bayu Sucahyo (Universitas Kristen Maranatha, 2019)
Abstract A leader's behavior is suspected to influence employee's subjective well-being (SWB) in achieving organizational goals through idealized influence, inspirational motivation, intellectual stimulation and individualized, consideration that provides an evaluation of the life and positive-negative affect on the employee. Transformational leadership (TFL) is leadership that supports followers thinking creatively by using new approaches or strategies, engaging employees in the decision making process, inspiring employee loyalty, and trying to understand individual employee differences to develop optimal potential. SWB is a global evaluation of themselves and positive and negative affect. The aim of research to determine the correlation of TFL and SWB on 66 production employees at PT. X Salatiga. The data collection is used by the multifactor leadership questionnaire scale (MLQ), satisfaction whit life scale (SWLS) and positive-negative affect scale (PANAS) to measure SWB. The result showed a positive correlation between TFL on SWB with r = 0.51 (p = 0.00). Keywords: Transformational leadership, subjective well-being, satisfaction, positive-negative affect